(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background: Respiratory distress is one of the most common causes of admission in neonatal intensive care units, it has multiple morbidities and depletes human and medical resources and it is an important cause of mortality and long term sequelea. Objective: Studying clinical progress of respiratory distress in neonates in neonatal intensive care unit in Tishreen university hospital. Materials and Methods: An analytic prospective study, we studied clinical progress of all neonates admitted with respiratory distress when admitted or happened during hospitalisation in neonatal intensive care unit in Tishreen university hospital between June 2022 and June 2023. We categorized the neonates by number of distress days, number of admission days, we studied the final diagnosis and the maternal history, we studied the complications and the final prognosis. We studied the relation between complications and final diagnosis and with prognosis. We used IBM SPSS Statistics (Version 25) program to do Statistics and analysis of results. Results: The study included 268 neonates admitted to neonatal intensive care unit in Tishreen university hospital, respiratory distress prevalance was 45.7%, the most common cause of respiratory distress was neonatal sepsis 44%, complications occurred 34.2%, mortality rate was 22.4%. Conclusion: Respiratory distress is an important cause of admission in neonatal intensive care unit and an important cause of complications and mortality so we have to study the clinical progress to limit morbidity and mortality.